(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
This study examines the level of Occupational Safety and Health (OSH) awareness among the staff of Sungai Petani Community College, using a quantitative method through a questionnaire involving 87 staff members. The main objective of this study is to measure the understanding and practices of OSH and to identify the factors that influence this level of awareness. Occupational Safety and Health is a critical aspect in ensuring a safe and healthy work environment, and its implementation in Malaysia is important for reducing the rate of accidents and work-related diseases. The study results indicate that the level of OSH awareness among staff is moderate, with several aspects requiring special attention for improvement. Specifically, factors such as inadequate OSH training, lack of support from management, and insufficient infrastructure have been identified as the main barriers to higher awareness. This study recommends that enhanced periodic training, improved management support, and better infrastructure provision are essential measures to increase awareness and safety practices in the workplace. These findings provide valuable insights to the management of Sungai Petani Community College in their efforts to improve the implementation of OSH and ensure the well-being of their staff. Further studies are recommended to assess the effectiveness of these initiatives in the long term and to expand the research to other educational institutions in Malaysia.